The geography and channels of diffusion at the world's technology frontier - Wolfgang Keller (Hamburg Institute of International Economics (HWWA), 2001)
Convergence in per capita income turns on whether technological knowledge spillovers are global or local. Global spillovers favor convergence, while a geographically limited scope of knowledge diffusion can lead to regional clusters of countries with persistently different levels of income per capita. This paper estimates the importance of geographic distance for technology diffusion, how this changed over time, and whether international trade, foreign direct investment, and communication flows serve as important channels of diffusion. The analysis is based on examining the productivity effects of R&D expenditures in the world's seven major industrialized countries between 1970 and 1995. First, I find that the scope of technology diffusion is severely limited by distance: the geographic half-life of technology, the distance at which half of the technology has disappeared, is estimated to be only 1,200 kilometers. Second, technological knowledge has become a lot more global from the early 1970s to the 1990s. Third, I estimate that trade patterns account for the majority of all differences in bilateral technology diffusion, whereas foreign direct investment and language skills differences contribute circa 15% each. Lastly, these three channels together account for almost the entire localization effect that would otherwise be attributed to geographic distance. – – Konvergenz beim Pro-Kopf-Einkommen hängt davon ab, ob technologische Wissensspillover global oder lokal sind. Während globale Spillover Konvergenz begünstigen, kann eine geographisch begrenzte Wissensdiffusion zu regionalen Länderverbünden mit anhaltenden Unterschieden in der Höhe des Pro-Kopf- Einkommens führen. In der vorliegenden Arbeit wird geschätzt, welche Bedeutung geographische Entfernung für Technologiediffusion hat, wie sich diese in der Zeit verändert hat und ob internationaler Handel, ausländische Direktinvestitionen und Kommunikation wichtige Diffusionswege bilden. Die Analyse basiert auf einer Untersuchung der Produktivitätseffekte von FuE-Ausgaben in den sieben größten Industrieländern der Welt zwischen 1970 und 1995. Es ergibt sich, erstens, ein starker Einfluß der Entfernung auf die Technologiediffusion: Der geographische Halbwert, gemessen an der Entfernung, bei der die Technologie sich zur Hälfte verflüchtigt, wird auf nur 1200 Kilometer geschätzt. Zweitens ist technologisches Wissen seit den frühen 70er Jahren deutlich globaler geworden. Drittens werden Unterschiede in der bilateralen Technologiediffusion überwiegend dem Handel zugerechnet, wohingegen ausländische Direktinvestitionen und unterschiedliche Sprachfertigkeiten jeweils ca. 15% beisteuern. Diese drei Übertragungswege machen zusammen fast den gesamten Lokalisierungseffekt aus, der sonst der geographischen Entfernung zugeschrieben würde.
Keywords: O3; F2; 330; Convergence; Divergence; Economic Geography; Total Factor Productivity; Technology Diffusion; International Trade; Foreign Direct Investment; Industrielle Forschung; Spillover-Effekt; Räumliche Innovationsdiffusion; international; Lokalisationseffekt; Außenwirtschaft; Schätzung; G7-Staaten